# 3(v-2)-5=-5(-5v+1)-6v

## Simple and best practice solution for 3(v-2)-5=-5(-5v+1)-6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3(v-2)-5=-5(-5v+1)-6v equation:

3(v-2)-5=-5(-5v+1)-6v
We move all terms to the left:
3(v-2)-5-(-5(-5v+1)-6v)=0
We multiply parentheses
3v-(-5(-5v+1)-6v)-6-5=0

We calculate terms in parentheses: -(-5(-5v+1)-6v), so:
-5(-5v+1)-6v
We add all the numbers together, and all the variables
-6v-5(-5v+1)
We multiply parentheses
-6v+25v-5
We add all the numbers together, and all the variables
19v-5
Back to the equation:
-(19v-5)

We add all the numbers together, and all the variables
3v-(19v-5)-11=0
We get rid of parentheses
3v-19v+5-11=0
We add all the numbers together, and all the variables
-16v-6=0
We move all terms containing v to the left, all other terms to the right
-16v=6
v=6/-16
v=-3/8

`